2013
DOI: 10.1097/01.icu.0000434534.32063.5c
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced uveitis

Abstract: Drug-induced uveitis has become increasingly recognized in association with a number of commonly used systemic, intraocular, and topical medications. A detailed history is often all that is needed to identify these important, often overlooked, and readily curable causes of uveitis. Most cases of drug-induced uveitis respond promptly to discontinuation of the suspected agent in conjunction with topical corticosteroid and cycloplegic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 132 publications
1
33
0
2
Order By: Relevance
“…Finally, several drugs with indications in diseases pertaining to different areas of medicine (such as cidofovir, anti-mycobacterial antibiotics, bisphosphonates, sulfonamides, tumor necrosis factor-a inhibitors, oral fluoroquinolones, and anti-vascular endothelial growth factor monoclonal antibodies) may uncommonly be associated with uveitis [48,49]. Often overlooked or misdiagnosed in the past, drug-induced uveitis is now increasingly recognized, thus becoming an important step of the uveitis diagnostic algorithm.…”
Section: 4%mentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, several drugs with indications in diseases pertaining to different areas of medicine (such as cidofovir, anti-mycobacterial antibiotics, bisphosphonates, sulfonamides, tumor necrosis factor-a inhibitors, oral fluoroquinolones, and anti-vascular endothelial growth factor monoclonal antibodies) may uncommonly be associated with uveitis [48,49]. Often overlooked or misdiagnosed in the past, drug-induced uveitis is now increasingly recognized, thus becoming an important step of the uveitis diagnostic algorithm.…”
Section: 4%mentioning
confidence: 97%
“…The second point is the need, of careful reviewing all current and previous drugs that the AU patient has been given, in which systemic, periocular, intravitreal, and topical medications have long been recognized as potentially responsible for drug-induced ocular inflammation [48][49][50]. The prompt recognition of drug-induced uveitis and the consequent discontinuation of the inciting drug usually result in regression of the ocular inflammatory process, thus avoiding the administration of additional, unnecessary drugs and the possible irreversible impairment of the visual function.…”
Section: Treatment Of Autoimmune Uveitismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ophthalmological outcome excluded Fuchs heterochromic iridocyclitis and Posner-Schlossman syndrome. In addition, several drugs including cidofovir and rifabutin are reported to induce uveitis [ 6 ]. In the present study, neither patient had taken those medicines during the period in which they contracted uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Several summaries of vaccine-associated uveitis have appeared over the past decade. [8][9][10][11][12][13][14][15] In the most comprehensive review from 2016, 10 Benage and Fraunfelder identified 289 cases using Medline literature searches and a systematic review of three surveillance systems: the National registry of Drug-Induced Ocular Side Effects (www.eyedrugregistry.com), the UMC, and the VAERS. Vaccination for hepatitis B virus (HBV), 15 either alone or in combination, was reported most frequently (40.5%), followed by immunization for human papillomavirus (HPV; 15.6%), 12 influenza virus (9.7%), Bacille Calmette-Guerin (BCG; 7.3%), measles-mumps-rubella (MMR) alone or in combination (4.8%), varicella virus alone or in combination (4.8%), and hepatitis A virus (HAV) alone or in combination (2.4%).…”
mentioning
confidence: 99%